PERANAN KEBIJAKAN FISKAL DALAM MENINGKATKAN PROGRAM PENGURANGAN STUNTING DI INDONESIA: STUDI KASUS KOTA BALIKPAPAN - Mahpud Sujai (ISJN Journal, 2020)
Health problems remain a formidable challenge in all over the world. Currently, millions of young children do not reach their full potential because of inadequate nutrition. Another challenge is the problem of poverty, where more than 700 million people still live on less than $ 1.90 per day. The current health condition based on stunting indicator of Indonesia is still lagging behind compare to those countries similar to Indonesia at the upper middle income country level. This can be seen from the Human Capital Index (HCI) score issued by the World Bank. Of the 157 countries surveyed, Indonesia is ranked 87th with a value of 0.53. Related to the issue of stunting, Indonesia's score of 0.664 is still far below the average score of upper middle income countries with a score of 0.867. These conditions need to be analysed more depth on the factors that cause the high stunting rate in Indonesia. The problem is Government of Indonesia has took several actions and allocated plenty of budget in the health sector including reducing stunting program, but the results still have not been encouraging. However, there are many cities that have been successfully reduced the stunting rate and Balikpapan City is one of the examples. This study aims to analyse the role of fiscal policy to promote stunting reduction program in Indonesia, case study Balikpapan City. Methodology uses in this study is a qualitative approach with descriptive analytical methods. The study was conducted by analysing secondary data and conducting a literature review. This article will discuss about how the local government can achieve successful indicators of reducing stunting by promoting effective fiscal policy as well as others supporting policies. Keywords: Stunting; Fiscal Policy; Local Government; Health